A Design for Gamified On-the-job Training - Bend, Julia (International Journal of Advanced Corporate Learning (iJAC), 2023)
The main purpose of this article is to review the factors that impact employee motivation in on-the-job training and the extent to which game mechanics can be used to increase motivation and expected learning outcomes. The choice for this topic is based on the lack of academic literature on gamification in the work environment – more so, relating to on-the-job training. Contrarily, the necessity for the improvement of user’s motivation in participating in such training programmes is already well established. This study presents the JT Framework for creating gamified on-the-job training. The baseline theories applied for the framework include: the flow theory, FODEM and Octalysis framework, which were combined with various motivational theories, game mechanics and studies on user types. The framework operates in the intersection within business ROI, user experience design and behavioural science, which need to be considered when evaluating the framework. In this research, a series of interviews were conducted to assess the framework model from the user’s perspective.